Основи створення та монтажу відео - Березова, А. С.; Хіміч, Є. О. (ХНУРЕ, 2025)
The work is devoted to the unique role of cinema as the richest means of expressing human emotions through the synthesis of visual, sound and textual elements. The process of creating video content from concept to post-processing is explored, where special attention is paid to the combination of the technical skill of the editor with creative vision. The importance of color correction, sound design and frame composition in shaping the mood and conveying the author's intention is analyzed. The report demonstrates the responsibility of video content creators in the information society and their ability to create a deep immersion of the viewer, allowing him to find his own understanding of the material.
Keywords: монтаж відео; створення відео